Three Bad Kids, One Loving Killer: Red China Noir in Blakean Symmetry - Sheng-mei Ma (Global Storytelling)
The twelve-episode Chinese TV series Yinmi de Jiaoluo (隱秘的角落 Hidden Corner, translated as The Bad Kids [2020]) dances on a Blakean “The Tyger and the Little Lamb” tightrope between childlike innocence and homicidal nihilism, between an art house sensibility and a pop culture chained to party propaganda. Amidst the flood of ethnocentric and jingoistic police procedurals “with Chinese characteristics” on TV, director Xin Shuang (辛爽) energizes his tour de force with a sensibility ranging far beyond Chinese shores, flirting with Western artists and metaphysical self-reflexiveness torn between good and evil, innocence and meaninglessness. Xin Shuang adapts Zijin Chen’s (紫金陈) eponymous web novel while imbuing the series with an off-kilter, haunting Yeatsian “terrible beauty” of violence and attraction.1 The Bad Kids made a killing not so much in profits as in the true art of Sino Noir, or Red China Noir. The eponymous “bad kids” blackmail a murderer to obtain funds for a life-saving surgery. Courting his own death, this “loving” killer saves one of the three kids from an asthma attack and spares the other two out of a fatherly compulsion to sire his own offspring, to pass on the legacy of revenge and guilt, to prolong his life—his afterlife, rather—as he confides: “I want you all to live—to live like me.” The Bad Kids’ Red China Noir teeters on a Blakean symmetry of love and hate, East and West.